Effect of strength training on female team sports athletes using isoinertial technology - Pérez Muñoz, S.; Morilla de la Riva, D.; Alonso García, G.; Sánchez Muñoz, A.; Albert García, FJ.; Rodríguez Cayetano, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2021)
The aim of this research is to analyse the effect of a four-week strength programme using isoinertial technology on performance improvement in women in team sports on an intermittent basis. The sample was composed of six women with an average age of 21 (±1.79 years). The tests of V-cut direction changes, explosive force counter movement jump and repeated sprint ability over 40 m were performed. The main results show that all the variables analysed are improved by training with isoinertial technology. They present significant differences (p<.05) in the variables of explosive strength and repeated sprint ability. Therefore, a strength training program using isoinertial technology during four weeks of training is sufficient for the improvement of direction changes, resistance to repeated sprinting and explosive leg strength.